Cognitive symptoms in schizophrenia: an analysis of awareness, assessment, and management practices among psychiatrists and primary care physicians - Agüera-Ortiz, Luis; Aragonés, Enric; Buch-Vicente, Bárbara; Mendive, Juan Manuel; Peña, Mercedes; Vieta, Eduard (Frontiers in Psychiatry, 2025)
IntroductionCognitive symptoms contribute to the worsening of functionality in people with schizophrenia. The objective of this study was to explore the current knowledge about cognitive symptoms (relevance, evaluation, and management) of psychiatrists and primary care physicians (PCPs) involved in the care of patients with schizophrenia in Spain.MethodsThe study was developed in two phases: a quantitative phase and a qualitative one. Both took place between November 2023 and January 2024. For the quantitative phase, an online questionnaire was developed and administered to 100 psychiatrists and 125 PCPs. In addition, further qualitative data were collected through individual semi-structured telephone interviews. Descriptive analyses and qualitative analyses (induction-deduction approach) were carried out.ResultsHealth professionals agreed that cognitive symptoms are present in patients with schizophrenia, with 75% of psychiatrists and 45% of PCPs acknowledging this. Both groups also considered the detection of these symptoms as crucial for improving patient functionality (89% psychiatrists vs 88% PCPs). However, over half of both psychiatrists and PCPs do not consistently evaluate cognitive symptoms, attributing this to factors such as time constraints, limited access to both pharmacological and non-pharmacological treatments, and a lack of effective diagnostic tools. PCPs additionally highlighted insufficient training regarding cognitive symptoms in schizophrenia. Both groups underscored the need for specific treatments for cognitive symptoms, with 87% agreement.ConclusionThis study offers an overview of the current understanding regarding the relevance, evaluation, and management of various cognitive symptoms according to clinical practice in Spain. The results highlight the necessity for enhanced guidelines, training, and improved access to effective treatments to address cognitive symptoms in patients with schizophrenia.